Education, over-education and wage inequality : evidence for Spain - Budría, Santiago (2015)
In this paper we use the European Community Household Panel to explore the connection between education, over-education, and wage-inequality in Spain for the period 1994-2001. Our central approach is based on quantile regression. We find that higher education is associated with higher wage dispersion. This indicates that an educational expansion towards higher education is expected, criteris paribus, to increase overall wage inequality. We find that over-education contributes to enlarge wage differentials within university graduates, still, over-education itself can not account for the positive association between higher education and wage dispersion. Finally, we show that over the last wage distribution of over-educated workers with university education became more dispersed. This process, together with an increasing proportion of over-educated workers, contributed to raise overall wage inequality through the within dimension.